Estudio de factibilidad para la creación de una empresa dedicada a la elaboración y comercialización de web sites para las empresas de la ciudad de Loja - Castillo León, Luis Enrique (2012)
This research work includes an extensive analysis on the feasibility of creating a company dedicated to the commercialization of Web Sites for the commercial sector in the city of Loja, our aim being to give a value to this technological tool, leveraging both the benefits advertising and exploitation of local labor. The methodology used for the preparation of this project involved the use of different methods such as scientific, deductive and inductive analytical, besides it was used as research techniques and the survey interview latter applied to a portion of the population being studied. This research has systematically all the steps and studies to help define the project's feasibility. The basic information is in the results of surveys of vendors and consumers in general. The content of this work was synthesized in the following: Market research which highlights the potential demand of 1255, effective demand for 1045, The plan also includes marketing of our product. The technical study establishes the size and location of the plant, project engineering also present the details of the production process using a flow chart to get the product to the final consumer. Then we present the administrative Study establishing the conditions for the formation of the company, organization, establishing hierarchical levels and functions manual for the proper performance of the company. It also presents a financial study in establishing investment and financing faced by investors to launch the project, defines the fundamental assumptions to analyze and determine its profitability, revenue and costs are calculated taking into account the price of the product, which is fully competitive with the prices of similar products in the market. The financial evaluation allows the investor to establish the feasibility of the project and make the decision to invest in this we have the following indicators: positive VAN of 129,721.80usd and TIR of 298.79%. The R(B/C) of 1.65 meaning that for every dollar you get 0.65 cents of profit, the capital recovery period of 1 years 1 months, 11 days, within the sensitivity analysis to a cost increase of 5% and a decrease in revenue of 10%. Subsequently, our research ends with the conclusions and recommendations that significantly help those who wish to invest in the project.